The 5Ms of Geriatrics in Gastroenterology: The Path to Creating Age-Friendly Care for Older Adults With Inflammatory Bowel Diseases and Cirrhosis. Issue 1 (12th January 2022) - Kochar, Bharati; Ufere, Nneka N.; Ritchie, Christine S.; Lai, Jennifer C.
Abstract : The number of Americans 65 years or older in 2060 will be more than double what it was in 2014. Approximately 40% of patients seen in gastroenterology (GI) and hepatology practices in the United States are 60 years or older. Adapting care delivery models, curating data on shifting risk-benefit decisions with geriatric syndromes, understanding appropriate assessments, and focusing on tailored implementation strategies are challenges that are actively confronting us as we provide care for a burgeoning population of older adults. Limited availability of geriatric specialists results in an onus of specialists caring for older adults, such as gastroenterologists, to innovate and develop tailored, comprehensive, and evidence-based care for adults in later life stages. In this article, we present the 5M framework from geriatrics to achieve age-friendly healthcare. The 5Ms are medications, mind, mobility, multicomplexity, and what matters most. We apply the 5M framework to 2 chronic conditions commonly encountered in clinical GI practice: inflammatory bowel diseases and cirrhosis. We highlight knowledge gaps and outline future directions to expand evidence-based care and advance the creation of age-friendly GI care.